Science Laboratory Inventory Management System of Bestlink College of the Philippines for Senior High School: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The research project refers to the various tools and equipment used by professionals or students working in a laboratory. Science laboratory equipment allows students to perform experiments rather than just read about them. Instead of taking monotonous notes, they can observe and complete exciting experiments. Hands-on learning often makes it easier to understand challenging theories and concepts. A science laboratory is a facility that provides controlled conditions in which scientific or technological research, experiments, and measurements may be performed. Laboratory services are provided in various settings: physicians’ offices, clinics, hospitals, and regional and national referral centers. In the planning stage, researchers in laboratory method students perform laboratory experiments by their own hands, individually or in small groups, under the supervision and guidance of their science (Physics, Chemistry, and Biology) teacher. So here, students are more active and involved than in the lecture–demonstration method, where the teacher performed experiments, and most students were just passive observers. Laboratory training is also often used to develop the skills needed for more advanced study or research.